Consumer Satisfaction to Improve Digital Marketing and Brand Image Through Service Quality in Coffee Shops (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
Digital marketing has become a new civilization of this era. With internet users reaching 185.3 million in Indonesia, more than half of them are online market consumers. While consumer satisfaction remains a key pillar of a business, it is also crucial in digital marketing. This satisfaction presents a challenge that can still be realized even in online buying and selling processes. Meanwhile, brand image is a factor that can influence consumer satisfaction, as a positive image built from a brand will stick in the minds of consumers. Similarly, service quality can serve as a means to achieve consumer satisfaction. However, these variables need to be examined when implemented in the digital or online space. This research aims to analyze the influence of Digital Marketing and Brand Image on Consumer Satisfaction through Service Quality. This quantitative research uses SEM (Structural Equation Model) methodology with 125 samples selected using purposive sampling from Starbucks consumers at Bintaro Plaza. The results of the regression test show that the digital marketing variable does not have an effect on service quality with a probability value of 0.894 > 0.05. The brand image variable has a direct effect on service quality with a probability of 0.00 < 0.05. The digital marketing variable has a direct effect on consumer satisfaction with a probability of 0.002 < 0.05. The brand image variable does not have an effect on consumer satisfaction because the probability is 0.44 > 0.05, and the service quality variable has an effect on consumer satisfaction because the probability is 0.003 < 0.05. The results of the indirect effect test show that digital marketing does not influence consumer satisfaction through service quality with a probability of 0.894 > 0.05; however, service quality can strongly intervene in the relationship between digital marketing and consumer satisfaction with a probability of 0.022 < 0.05.